National trends in Azithromycin consumption during 2017–2023 in Kazakhstan: impact of the COVID-19 pandemic and the imperative for enhanced clinical guidelines - Laura Kassym; Assiya Kussainova; Daniil Semenov; Ainur Aimurziyeva; Saltanat Uzbekova; Yuliya Semenova (Scientific Reports)
Abstract Antibiotic resistance (AMR) has reached critical levels globally, especially in developing economies like Kazakhstan, largely due to improper antibiotic use. The aim of this study was to examine seven years of azithromycin sales data in Kazakhstan to uncover consumption patterns during the COVID-19 pandemic and develop effective strategies to combat AMR. This study analyzes two data sets: one from a comprehensive review of documents regulating azithromycin use in Kazakhstan. The second data set consists of a pharmaco-epidemiological analysis of azithromycin consumption from procurement data provided by Vi-ORTIS. Azithromycin consumption (ATC group J01FA10) from 2017 to 2023 was measured in DDD/1000 inhabitants/day (DID) using the ATC/DDD methodology. Azithromycin is extensively used in adult and pediatric care in Kazakhstan. Its consumption, measured in DDD per 1,000 inhabitants, surged in 2020 with the COVID-19 outbreak. The steady annual increase in “Watch” antibiotics, including azithromycin, should alarm Kazakhstan’s healthcare system. This trend highlights the need for stronger stewardship programs, targeted interventions, and comprehensive monitoring to prevent antibiotic overuse and misuse. Addressing this is crucial to maintaining antibiotic effectiveness and safeguarding public health.